1979
DOI: 10.1007/bf00345996
|View full text |Cite
|
Sign up to set email alerts
|

Litter accumulation in woodlands contaminated by Pb, Zn, Cd and Cu

Abstract: Close to a primary lead-zinc-cadmium smelter the standing crop of litter in woodlands was found to be elevated relative to more distant sites. The total litter accumulation is similar to that from contaminated sites reported by other authors but in this case the concentrations of heavy metals are considerably lower than those reported for other sites. Evidence is provided to support the hypothesis that within the woodlands studied, litter accumulation is not closely pH dependent, but is clearly related to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(33 citation statements)
references
References 17 publications
5
28
0
Order By: Relevance
“…1995, Dumat et al 2006. Early studies on the effects of heavy metals on soil respiration show the inhibitory effects of Pb, Zn, Cd or Cu (Williams et al 1977, Coughtrey et al 1979. Our data indicate Table 3.…”
Section: Discussionsupporting
confidence: 52%
“…1995, Dumat et al 2006. Early studies on the effects of heavy metals on soil respiration show the inhibitory effects of Pb, Zn, Cd or Cu (Williams et al 1977, Coughtrey et al 1979. Our data indicate Table 3.…”
Section: Discussionsupporting
confidence: 52%
“…However, heavy metals adsorbed onto organic matter in soil are assumed to play an important role in the suppression of organic matter decomposition. It has been reported that soil respiration and enzymatic activities decreased as the concentration of total heavy metals increased in the soil around a brass foundry (Tyler 1974;Ebregt and Boldewijn 1977), and that litter accumulation is clearly related to both Cd and Zn concentrations in litter (Coughtrey et al 1979). The inhibition of organic matter decomposition in soil strongly contaminated with heavy metals may be due to the adsorption of heavy metals onto organic matter.…”
Section: Pseudomonas Put~damentioning
confidence: 99%
“…All sudden environmental changes are amenable to the local extinction of species and, thus, above some given threshold of tolerance, of functions (Barros et al, 2001). Local changes in humus forms and important soil functional processes have been repeatedly described under the influence of pesticide and fertilizer use (Barratt, 1967;Topoliantz et al, 2000), heavy metal deposition (Coughtrey et al, 1979;Gillet and Ponge, 2002), plantation (Nihlgård, 1971;Muys and Lust, 1993), fire (Majer, 1984;Zackrisson et al, 1996) and liming (Deleporte and Tillier, 1999), among others. Some of these changes are irreversible, i.e.…”
Section: Biodiversity and Ecosystem Processes: Humus Forms May Help Tmentioning
confidence: 99%